Harmonisasi Regulasi Nasional dalam Pengelolaan dan Pemanfaatan Tanah dalam Perpektif Teori Sistem Hukum - Kayla Vania Gita Putri; Akhmaddhian, Suwari (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2025)
This study aims to analyze the harmonization of national regulations on land management and utilization in Indonesia by examining the relationships between land regulations and the challenges of their implementation, both vertically and horizontally. Using a normative juridical method supported by a qualitative approach, this study analyzes the alignment between the Basic Agrarian Law (UUPA) as the legal umbrella for agrarian affairs and sectoral regulations governing forestry, mining, spatial planning, the environment, and investment. The results indicate that despite the comprehensive normative framework for land management, regulatory disharmony persists due to overlapping authority, differing interpretations of regulations, and institutional fragmentation. This situation results in uncertainty over land status, slowed development, and increased agrarian conflict. The conclusions of this study emphasize the importance of regulatory harmonization through the integration of legal substance, institutional alignment, optimization of the national land database, and improvement of legal culture to ensure effective, equitable, and sustainable land governance.